A Genuine Friend Wishes to be a Debtor: John Chrysostom’s Discourse on Almsgiving Reinterpreted - Verhoeff, Maria (Sacris erudiri, 2013)
This article presents a systematic analysis of John Chrysostom’s concept of God as debtor, which is primarily used in his discourse on almsgiving. On the basis of John’s own suggestion, it is proposed that friendship with God is the appropriate interpretative framework for understanding how God can become one’s debtor. Chrysostom’s idea of friendship with God is explored in relation to his views about merchandise against the background of both Graeco-Roman euergetism and aspects of the Judeo-Christian tradition on gift-giving. It is argued that despite his abundant use of the economic language of lending and banking, Chrysostom’s dominant emphasis falls on the cultivation of friendship with God, rather than on almsgiving as a redemptive activity in itself.